공동주택 리모델링 세대평면의 계획특성과 법규변화 관계에 관한 연구 - 김수암(Soo-Am Kim); 백정훈(Cheong-Hoon Baek); 양현정(Hyeon-Jeong Yang) (KIEAE Journal, 2020)
Purpose: Since the remodeling system was introduced in Korea in 2001, the plan for the remodeling of apartment housings has changed. The purpose of this study is to analyze the contents and relationships of how the remodeling unit plan has changed with the remodeling system change. Method: The research method was to analyze the case collection and laws of 14 complexes with remodeling in Seoul and compare the contents with each other. The contents of this study were divided into phases by analyzing the extension criteria of regulations affecting the unit plan change. After examining the changes and characteristics of the plan, the relationship between the change of the law and the unit plan change was analyzed. Result: First, the phase could be classified into three categories based on the change in the standard of regulations affecting the unit plan. Second, the unit plan layout features can be classified into six categories: block type, layout, extension direction, bay number change, living direction, cross section, and access type. Third, the relationship between the phase change and the plan change of the extension standard of the regulation was analyzed as the layout change based on the internal change of the unit in the first phase and the expansion area of t he second phase. The results of this study can be referred to future 3rd phase remodeling unit plan design. KCI Citation Count: 0